2014
DOI: 10.4161/auto.27901
|View full text |Cite
|
Sign up to set email alerts
|

Acidic extracellular pH neutralizes the autophagy-inhibiting activity of chloroquine

Abstract: Acidic pH is an important feature of tumor microenvironment and a major determinant of tumor progression. We reported that cancer cells upregulate autophagy as a survival mechanism to acidic stress. Inhibition of autophagy by administration of chloroquine (CQ) in combination anticancer therapies is currently evaluated in clinical trials. We observed in 3 different human cancer cell lines cultured at acidic pH that autophagic flux is not blocked by CQ. This was consistent with a complete resistance to CQ toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(161 citation statements)
references
References 53 publications
2
155
0
1
Order By: Relevance
“…However, its clinical usefulness is severely limited because highly effective doses are required [13][14][15] to compensate for its nonselective distribution in vivo and its inability to cross tumor cell membranes effectively in the acidic tumor microenvironment. 22 Here we tried to avert all 3 problems by encapsulating HCQ in PEGylated liposomes coated with TR peptide. We show using in vitro and in vivo approaches that HCQ/Lip-TR specifically targets B16F10 tumors and efficiently accumulates HCQ within tumor cells and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its clinical usefulness is severely limited because highly effective doses are required [13][14][15] to compensate for its nonselective distribution in vivo and its inability to cross tumor cell membranes effectively in the acidic tumor microenvironment. 22 Here we tried to avert all 3 problems by encapsulating HCQ in PEGylated liposomes coated with TR peptide. We show using in vitro and in vivo approaches that HCQ/Lip-TR specifically targets B16F10 tumors and efficiently accumulates HCQ within tumor cells and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…3D), the TR peptide appears to help overcome the pH barrier that normally prevents efficient internalization of HCQ under acidic conditions. Indeed, acidic extracellular pH inhibits chloroquine endocytosis, 22 and its structure is similar to that of HCQ. Taken together, our results suggest that the TR peptide supports efficient delivery of HCQ/ Lip-TR preferentially to tumors expressing high levels of the ITGAV-ITGB3/integrin a v b 3 receptor in an acidic microenvironment.…”
Section: Delivery Of Hcq Into Tumor Cells In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Chloroquine can affect lysosomal activity and induce accumulation of LC3-II only at the physiological pH 7.4, but not at acidic pH conditions. 36 Therefore, we speculated that culture medium was at acidic pH when cells had been cultured for more than 36 hours. Ammonium chloride did not inhibit lysosomal activity under acidic extracellular pH.…”
Section: Discussionmentioning
confidence: 99%
“…Acute and chronic exposure to low pH promotes high level of autophagic activity, and this sustains cell survival and aggressiveness, while the pharmacological inhibition of autophagy in such acidic tumor cells reduces their ability to survive [55]. Furthermore, it was demonstrated that acidosis blocks the inhibitory activity of chloroquine on autophagy, thus chloroquine does not result effective in tumor treatment [56]. Up-regulation of autophagy-mediated degradation and recycling of cellular substrates by acidic cancer cells can support metabolic pathways considering that an acidic microenvironment is generally characterized by low nutrients and oxygen.…”
Section: How Low Ph May Contribute To Dormancy Of Tumor Cells Aciditymentioning
confidence: 99%